Praktik Supervisi Klinis di MA Daruttauhid: Pendekatan, Kendala, dan Implikasinya terhadap Pembelajaran - Dini Nabila Faiz; Shobihatul Fitroh Noviyanti; Haniyah; Anisah Najwa Mumtaza; Sayyid Zuhdan Naufal (Al-Kindi, 2026)
This study looks at how clinical supervision can affect teachers' performance and improve their teaching skills. It also examines the role of the school principal in this process, the challenges faced, and effective solutions at MA Daruttauhid. Therefore, this study aims to analyze the models used, the approaches taken, and the practices in the field. The method used in this study is qualitative, which includes observing and having direct interviews with research subjects like the school principal, teachers, and students. This study is also backed by a review of literature to provide comparison material, explore, and combine different scientific findings from the past. The findings and discussion show that the teachers at MA Daruttauhid believe that the clinical supervision they receive is very helpful in improving their teaching skills. Mereka tidak menganggapnya sebagai beban atau menakutkan. Therefore, the implementation of clinical supervision can greatly help improve the quality of teaching if it is managed well. This requires teamwork between external supervisors and the school principal, who acts as the internal supervisor. It also needs solution-focused leadership and motivated teachers who want to improve themselves